2005
DOI: 10.1086/466529
|View full text |Cite
|
Sign up to set email alerts
|

Herpesvirus Infections in Solid Organ Transplant Patients at High Risk of Primary Cytomegalovirus Disease

Abstract: The epidemiology of infections with 5 human herpesviruses (HHVs) (HHV-6, HHV-7, HHV-8, varicella zoster virus [VZV], and Epstein-Barr virus [EBV]) was investigated during the first year after solid organ transplantation in 263 patients who received oral ganciclovir or valganciclovir prophylaxis. HHV-6B DNAemia was uncommon, HHV-6A DNAemia was not observed, and HHV-7 DNAemia was prevalent. HHV-6 and HHV-7 DNAemia were not significantly associated with cytomegalovirus (CMV) disease, although a trend toward highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
68
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(76 citation statements)
references
References 46 publications
4
68
4
Order By: Relevance
“…Thus, it has been suggested that the syndrome of febrile illness with myelosuppression and rash after transplantation be termed as b-herpesvirus syndrome while the specific viral etiology is being investigated [48] Co-infections with HHV-6 and CMV have been demonstrated in these cases [47] . However, a recent large study of solid organ transplant recipients demonstrated that HHV-6 was not significantly associated with any clinical symptoms during CMV disease [41] .…”
Section: Clinical Syndromes Associated With Hhv-6 Infection After LIVmentioning
confidence: 97%
See 2 more Smart Citations
“…Thus, it has been suggested that the syndrome of febrile illness with myelosuppression and rash after transplantation be termed as b-herpesvirus syndrome while the specific viral etiology is being investigated [48] Co-infections with HHV-6 and CMV have been demonstrated in these cases [47] . However, a recent large study of solid organ transplant recipients demonstrated that HHV-6 was not significantly associated with any clinical symptoms during CMV disease [41] .…”
Section: Clinical Syndromes Associated With Hhv-6 Infection After LIVmentioning
confidence: 97%
“…The direct clinical manifestations due to HHV-6 include a febrile illness with or without rash, myelosuppression, hepatitis, pneumonitis and neurological diseases [33,[36][37][38] . The indirect effects attributed to HHV-6 include an exacerbation of cytomegalovirus (CMV) disease, an increased severity of hepatitis C virus (HCV) recurrence, an increased risk of other opportunistic infections, allograft dysfunction, and acute cellular rejection (Table 1) [33,36,[39][40][41][42][43][44][45] . Direct HHV-6 effects Fever and rash: The most frequently reported clinical presentation of HHV-6 infection after liver transplantation is a febrile illness that can be associated with a rash [34,36,46] .…”
Section: Clinical Syndromes Associated With Hhv-6 Infection After LIVmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Many investigators have studied the clinical features of HHV-6 infection in liver transplant recipients, using viral isolation, [3][4][5][6][7][8][9] antigenemia assay, [10][11][12][13][14] serological analysis, 15,16 and molecular analysis such as real-time polymerase chain reaction (PCR). [17][18][19][20][21][22] Several clinical features, including fever, 5,6,8,10 encephalitis, 7,23 CMV disease, 15,17,18 fungal infection, 7 graft dysfunction, 10,11,22 and hepatitis C virus (HCV) recurrence 9,19 after transplantation, have been suggested as clinical manifestations due to HHV-6 infection. However, the precise clinical features of HHV-6 reactivation remain unknown because evaluating active HHV-6 infection in transplant recipients is difficult.…”
mentioning
confidence: 99%
“…For all other herpesviruses, in-house real-time polymerase chain reaction assays based on the Lightcycler format were performed on stored whole blood samples using methods previously described. 17 The lower limit of detection for these assays was ϳ5 copies/mL of whole blood. CMV viral load testing was done in all patients while other herpesviruses were tested for in patients who provided consent for these specific tests.…”
Section: Laboratory Testingmentioning
confidence: 99%